1966
DOI: 10.1021/bi00871a040
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Citrinin in Penicillium citrinum. I. Production and Degradation of Citrinin*

Abstract: A study of the production of citrinin by Aspergillus niceus and Penicillium citrinum Thom is described. Plots of citrinin production cs. time show that the A. niceus strain investigated produces a higher yield of the antibiotic than does the Penicillium sp. A stepwise chemical degradation of citrinin which is readily adaptable to radioactive tracer techniques is reported. The process involves the degradation of this substance to the known 3-(2-methyl-3,5-dimethoxyphenyl)-2-butanone which is then degraded furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Thus, production runs may be terminated at the convenience of the researcher rather than according to a predetermined or rigid time schedule. Surprisingly, yields were comparable to those scaled up (by calculation) from smaller systems (5,11,15,17) rather than diminished as often occurs when small systems are scaled up. About 45 to 50% of the crude citrinin was recoverable in pure form by the method used (5).…”
mentioning
confidence: 72%
“…Thus, production runs may be terminated at the convenience of the researcher rather than according to a predetermined or rigid time schedule. Surprisingly, yields were comparable to those scaled up (by calculation) from smaller systems (5,11,15,17) rather than diminished as often occurs when small systems are scaled up. About 45 to 50% of the crude citrinin was recoverable in pure form by the method used (5).…”
mentioning
confidence: 72%
“…To date, no methods have been reported for the production and analysis of citrinin in corn; most production methods utilize liquid media (4,6,14,17). The fact that Scott et al (16) have found as much as 0.08 g of citrinin per kg of naturally contaminated wheat suggests that grains could possibly be a good substrate for citrinin production.…”
mentioning
confidence: 99%
“…Crystalline ochratoxin A was obtained from Macor Chemicals Ltd., Jerusalem, Israel. Crystalline citrinin was obtained from Aspergillus niveus NRRL 1955 (strain kindly supplied by C. W. Hesseltine, Northern Regional Research Laboratory, USDA, Peoria, Ill.), according to the procedure of Rodig et al (9). Malting and brewing.…”
mentioning
confidence: 99%